Death in paradise. Season nine [videorecording (DVD)] - O'Hanlon, Ardal; Little, Ralf, 1981-; Legastelois-Bidé, Aude; Bakare, Tobi (BBC, 2020)
Detective Inspector Jack Mooney and his team-now including the new arrival DI Neville Parker--continue to fight crime on their Caribbean island.